THE USE OF MODERN METHODS IN TEACHING FOREIGN LANGUAGES - Abdirasilova Sarvinoz Ravshan qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: The rapid development of globalization, information technologies, and intercultural communication has significantly increased the importance of foreign language  education.  Traditional  teaching  methods  are  gradually  being  replaced  by modern  pedagogical  approaches  that  focus  on  learner-centered  instruction, communicative  competence,  creativity,  and  technological  integration.  This  article examines  the  use  of  modern  methods  in  teaching  foreign  languages,  including communicative  language  teaching,  task-based  learning,  project-based  learning, blended  learning,  gamification,  and  digital  technologies.  The  study  analyzes  the effectiveness of these approaches in improving learners’ speaking, listening, reading, and writing skills.